Fluoroquinolone antibacterial drugs: Review of physicochemical problems, analysis techniques, and solutions - Ainurofiq, Ahmad; Syahrul, Anas; Widayati, Aulianingrum; Fitriastuti, Rafifah; Herawati, Zainab (Asia-Pacific Journal of Science and Technology, 2022)
Fluoroquinolones are a class of second-generation quinolone antibiotics. Some fluoroquinolone drugs have problems concerning their photostability. There are also problems of physicochemical properties related to hygroscopicity, incompatibility with its excipient during formulation, and interactions with other drugs. Efforts to increase photostability and reduce hygroscopicity continue, as do efforts to solve the problem of incompatibility with certain excipients and interactions with other drugs. If these issues are not resolved, they will cause problems during their manufacture and administration to patients, which will affect the therapeutic value of the drugs. Efforts to improve the stability of fluoroquinolones have been reported, such as preparing co-crystals and complexes with polymers. This research has shown potential, but the challenge is to have a deeper understanding of the physicochemical characteristics of fluoroquinolone drugs have insight into other problem-solving approaches with respect to the composition of the formula, the manufacturing process, equipment, and even packaging used in formulating the drug. A deeper understanding the problems will lead to appropriate solutions, such as improving photostability, reducing hygroscopicity, choosing excipients during formulation, and using the correct drug.